Standard specification for aluminum bronze sheet, strip, and rolled bar
This specification establishes the requirements for Copper Alloy UNS Nos. C61300 and C61400 aluminum bronze sheet, strip, and rolled bar. The products made to this specification are commonly used for drawing, forming, stamping, and bending applications and are not intended for electrical applications.